Mabbolo Possi Bola: Synthesizing Local Cultural Practices and the Living Sunnah in Bugis-Mandar Tradition - Rafid A., Noercholis; Yunan, Muhammad; Nurpadila, Nurpadila; L, Sudirman; Naufal, Aulia (IAIN Palangka Raya, 2026)
This study examines the prayer ritual at the central pillar of the the house (mabbalo possi bola or posi’ boyang) among the Bugis and Mandar communities through the perspective of Living Sunnah. It aims to explain the meaning, practice, and religious relevance of the ritual in local Muslim society. This research employs a descriptive qualitative approach using normative theological and ethnographic methods. The study was conducted in Luyo District (Polewali Mandar) and Pammana District (Wajo). Data were collected through in-depth interviews, participant observation, and documentation, and analyzed through triangulation. The findings show that the ritual combines the recitation of basmalah, shalawat, adhān, Barzanji, and supplications as expressions of gratitude and prayers for protection to Allah, while strengthening social solidarity through communal cooperation and shared meals. Interview findings also indicate that the tradition is understood by the community as not contradicting Islamic principles and may be categorized as ‘urf ṣaḥīḥ because it remains consistent with the principle of tawḥīd.